Clinical and epidemiologic characteristics in patients hospitalized due to heart failure - Lucia Nivia Turro Mesa; Germán del Río Caballero; Eloy Turro Caró; Germán del Río Mesa; Rita María Mesa Valiente (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Heart failure is a cause of frequent hospitalization and has led to an increase in mortality.  Objective: To characterize patients hospitalized due to heart failure according to clinical and epidemiologic variables.  Methods: A descriptive and cross-sectional study of 100 patients with heart failure was carried out, who were admitted in the cardiology room of Saturnino Lora Teaching Clinical Surgical Provincial Hospital in Santiago de Cuba, from September, 2018 to the same month in 2020. Results: The disease reached higher frequency from the 60 years of age. The proportion of women was superior in the intermediate age and hypertension prevailed as risk factor. The main symptoms and signs found were the dyspnea (81.0 %), peripheral edemas (63.0 %), crakle rale (51.0 %) and heart murmurs (33.0 %). In the echocardiogram, the ejection fraction was shown conserved in 54.0 % and reduced in 46.0 %. The main electrocardiographic findings were the fasciculus and bundle branch heart blocking (31.0 %) and flutter atrial fibrillation (21.0 %).  Conclusions: Heart failure prevailed in elderly and hypertension was the main risk factor in its appearance. The characteristics found can be useful for the stratification, prediction and establishment of more effective therapeutic rules in the patients admitted with the mentioned affection.